2015
DOI: 10.1002/esp.3836
|View full text |Cite
|
Sign up to set email alerts
|

The extreme 2013/2014 winter storms: hydrodynamic forcing and coastal response along the southwest coast of England

Abstract: The southwest coast of England was subjected to an unusually energetic sequence of Atlantic storms during the 2013/2014 winter, with the 8-week period from mid-December to mid-February representing the most energetic period since at least 1953. A regional analysis of the hydrodynamic forcing and morphological response of these storms along the SW coast of England highlighted the importance of both storm-and site-specific conditions.The key factor that controls the Atlantic storm wave conditions along the south… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
174
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 204 publications
(182 citation statements)
references
References 37 publications
5
174
0
3
Order By: Relevance
“…An interesting feature is the occurrence of the exceptional winter of 2013-2014, at the end of the period of analysis, which offered record-breaking numbers of storms, wave energy, cyclonic activity, and morphological impacts on the coast of France and the UK [48,49]. Analysis is underway on the effects of those storms during the winter of 2014, which also offer a picture of extraordinary damage along the northern coast of Spain in both the natural environment, and on infrastructure and equipment, the restoration of which was worth around €70 million [20].…”
Section: Discussionmentioning
confidence: 99%
“…An interesting feature is the occurrence of the exceptional winter of 2013-2014, at the end of the period of analysis, which offered record-breaking numbers of storms, wave energy, cyclonic activity, and morphological impacts on the coast of France and the UK [48,49]. Analysis is underway on the effects of those storms during the winter of 2014, which also offer a picture of extraordinary damage along the northern coast of Spain in both the natural environment, and on infrastructure and equipment, the restoration of which was worth around €70 million [20].…”
Section: Discussionmentioning
confidence: 99%
“…At the other end of the spectrum, beaches with similar wave exposure may exhibit similar links with weather regimes. Comparative data presented in Masselink et al (2016aMasselink et al ( , 2016b reveal that shoreline change patterns on interannual timescales are very similar at Perranporth beach (SW England) and Truc Vert beach. Future work should involve application of this statistical model to other coasts exposed to waves generated over the North Atlantic Ocean.…”
Section: Weather Regime-driven Shoreline Modelmentioning
confidence: 93%
“…Previous studies about the influence of storms on coastal soft-sediment ecosystems have shown that storms may have stronger impacts on environmental features than on the fauna (e.g., Saloman & Naughton, 1984; Cochôa, Lorenzi & Borzone, 2006; Alves & Pezzuto, 2009; Harris et al, 2011), and that offshore sediment transport is the dominant geo-morphological response of sedimentary shores to increased wave energy (Masselink et al, 2016). These studies were, however, mostly done on exposed ocean beaches, habitats with fewer species that are well adapted to high-energy conditions (Brown, 1996; Schlacher et al, 2008).…”
Section: Discussionmentioning
confidence: 99%